Review of A musica e um jogo de crianca by Francois Delalande - Moreira, Tamya [UNESP] (Assoc Nac Pesquisa & Pos-graduacao & Musica, 2021)
This review aims to present the book A musica e um jogo de crianca by Francois Delalande, whose first edition in Portuguese dates from 2019. We indicate aspects as to why this book is a useful reference source for Music Education in addition to establishing its connection to other works and providing the context of its production. The pillars of Delalandian thought are highlighted, namely: developmental psychology, aesthetics, and ethnomusicology. In dialogue with these areas, Delalande presents a pedagogical proposal, the pedagogy of musical awakening. The objective of this review is to contribute to the reading and discussion of this work in Brazil, since for decades, having no translation, its circulation was restricted and can now be accessed by a greater number of people.
Keywords: Music education; Francois Delalande; Pedagogy of musical awakening; Musique concrete